Patompes Stunting: Pelatihan Kader Posyandu sebagai Upaya Menurunkan Angka Stunting di Desa Sumberjambe Kabupaten Jember - Nurika, Globila; Adi, Dhuha Itsnanisa; Baroya, Ni’mal; Khinanti, Citra Anggun; Rahmaddani, Rafi Indra; Fatima, Riham; Listianingrum, Meyhilda Putri Dwi; Putri, Etania Febry Kirana; Qonitatillah, Qonitatillah; Astiningsih, Dwi Yuli; Naziha, Fikri; Rosydah, Shofiyah Nur; Putri, Aninda Dyah Hayu Pinasti; Sari, Novita; Rakhman, Fani Khairunnisa (UNEJ e-Proceeding, 2023)
Background: The focus on reducing stunting rates in Indonesia is accelerating, especially in Jember Regency, which has the highest stunting rate in East Java Province. Findings of anthropometric measurement errors on under-fives and toddlers carried out by posyandu cadres can impact stunting status determination errors. Therefore, the purpose of this community service activity is to increase the understanding and skills of posyandu cadres regarding the problem of stunting nutrition, anthropometric measurements with the main indicators measuring Body Length and Height, as well as filling out the Kartu Menuju Sehat and interpretation of stunting nutritional status. Method: This activity was carried out using lecture, discussion, demonstration, and practice methods with a target of 24 posyandu cadres. Evaluation of this activity was carried out using the pre-test and post-test methods, as well as observation. Educational media in the form of the PATOMPES STUNTING Pocket Book was used in this activity. Results: This activity was attended by 19 posyandu cadres with an adequacy performance value exceeding 75%. The first activity in the form of education using lecture and demonstration methods was carried out for 30 minutes and resulted in an increase in target knowledge of 11.05% based on pre-test and post-test evaluations. The second activity in the form of practicing anthropometric measurements and filling out the Kartu Menuju Sehat, also showed an increase in the skills of posyandu cadres. Conclusion: This community service activity was effective in understanding and skills of Posyandu cadres in Sumberpakem Village regarding stunting nutrition, anthropometric measurements with the main indicators measuring Body Length and Height, as well as filling out the Kartu Menuju Sehat and interpretation of stunting nutritional status.Keywords: anthropometric measurements of stunting, posyandu cadres, stunting education.